Kepailitan Suatu Solusi dalam Memaksimalkan Penagihan Piutang Kreditur (Lex Jurnalica, 2010)
World recession much impact on the business world. Bankruptcy is one result of the recession that occurred since the onset of debts due to the dispute are unable to pay its debts. Bankruptcy is a solution to solve these problems because of bankruptcy give assurance to creditors to recover receivables and also provide protection to the debtor in order to divide the pari pasu to all creditors. The purpose of this paper is to discuss theoretically that bankruptcy can be a solution to resolve the dispute debts that can deliver maximum results to return receivables Creditor. Research methods in this paper is the juridical normative, that is by researching the literature, both primary law materials and secondary legal materials. Research is also conducted on the principles of law and rules of law relating to dispute resolution, bankruptcy law and the law of the engagement. Bankruptcy is a way of resolving the dispute by way of settlement, which will be divided budel bankruptcy to its creditors in Parai tubs prorate parte. Bankruptcy as a means of obtaining repayment of debt by the creditor, because quite a lot of creditors while the debtor is not sufficient assets to pay off all creditors. Settlement of disputes between the Debtor and Creditor conducted in a fair, fast, open and effective, where the principle of fairness and legal certainty are the two principles is premised in the dispute settlement debt problems through bankruptcy and Suspension of Payment.Keywords: The Bankruptcy, The Solution, Return of the Debt.